Perancangan Dan Penataan Penerangan Jalan Umum Dengan Aplikasi Dialux evo 8.2 Di Jalan Depok Cilodong - JUARA MANGAPUL TAMBUNAN; Albert Gifson Hutajulu; Hendrianto Husada (Energi & Kelistrikan, 2020)
The increase in population, urban development and road construction are the demands of many communities in obtaining public street lighting for road users by providing better services. Public street lighting has become a necessity for many people, which is very important for two-wheeled, four-wheeled, and many-wheeled drivers for safety and comfort in traffic, especially at night. Therefore, the authors conducted a new research design by arranging public street lighting in the area of ​​the Depok Cilodong highway, with the aim of providing the beauty of the road environment by the model of the arrangement and installation of poles, pole height and PJU lamp models to the road body. Its uniqueness is seen from the perspective of the side of social and environmental impacts that are generally not seen by the local government and the level of evenness of road lighting on road materials is still lacking, so that the impact on the road user community is better and more modern. The method used with the Dialux EVO 8.2 Program for short road lengths can choose street lights taken from the IES Lighting data on the 10W Eco Led, 10 VAC Milky Way, which is installed with a height of 8 meters with a distance between poles 15 meters with a large amount of procurement allows for high costs. For the long distance of the road, you can use the 20W Led Bimasakti Eco street light, 10 VAC, which is installed with a height of 8 meters and 20 meters between the poles. So by analyzing the selection criteria, it is capable of producing street lighting with lighting levels in accordance with SNI 7391-2008 and considering the quantity of material procurement as well as the tipping point which has an impact on financing for installation services.